INSTITUTIONALISING JAZZ EDUCATION IN CONTEMPORARY CHINA: A QUALITATIVE EXPLORATION OF GLOCALISATION AND PEDAGOGICAL INNOVATION - Lu , Lu; Salleh , Marzelan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Despite the rapid expansion of jazz education in Chinese higher education institutions (HEIs), the development of teaching systems and professional competencies has lagged. This study examines how institutional expansion, pedagogical practices, and learning environments shape the localization of jazz education. Employing a multi-source qualitative design including documentary analysis, interviews with senior educators, and field observations, the research reveals a "decoupling between institutionalization and quality." Specifically, the proliferation of degrees outpaces the maturity of the faculty-textbook-training paradigm, a discrepancy particularly pronounced in vocal jazz. Furthermore, given the scarcity of formal resources, masterclasses and workshops serve a compensatory function by facilitating demonstrative training and the transfer of tacit knowledge. These processes rely on a multi-tiered chain connecting HEIs, private institutions, and early education. Consequently, this study proposes a mechanistic framework to guide curriculum and faculty development in emerging music disciplines.